2018
DOI: 10.1002/pc.24910
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilically modified poly(vinylidene fluoride) nanofibers incorporating cellulose acetate fabricated by colloidal electrospinning for future tissue‐regeneration applications

Abstract: A composite consisting of mechanically strong Poly(vinylidene fluoride) (PVDF) and biochemically favorable Cellulose acetate (CA) nanofibers can be considered as an excellent choice due to their excellent mechanical properties of PVDF and desirable biological properties of CA. However, preparing nanofibers of composites, involving CA requires the use of harsh acidic solutions and high temperatures, which can have serious consequences on a bio‐aspect of CA. In this study, we have successfully prepared suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Surgical meshes and sutures require non-reactivity, whereas wound-healing applications require piezoelectricity [ 21 ]. Hence, this material is considered suitable for various biomedical applications such as tissue engineering [ 22 , 23 , 24 , 25 , 26 , 27 ], physiological signal detection [ 28 , 29 , 30 , 31 , 32 ], and antimicrobial and antifouling material development [ 22 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, it is difficult to produce coatings for biomedical applications using PVDF because it does not form smooth films and exhibits issues in adhesion with other substrates.…”
Section: Biopolymer Coatings For Surface Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical meshes and sutures require non-reactivity, whereas wound-healing applications require piezoelectricity [ 21 ]. Hence, this material is considered suitable for various biomedical applications such as tissue engineering [ 22 , 23 , 24 , 25 , 26 , 27 ], physiological signal detection [ 28 , 29 , 30 , 31 , 32 ], and antimicrobial and antifouling material development [ 22 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, it is difficult to produce coatings for biomedical applications using PVDF because it does not form smooth films and exhibits issues in adhesion with other substrates.…”
Section: Biopolymer Coatings For Surface Modificationmentioning
confidence: 99%
“…Yin et al reviewed studies reporting the application of PVDF and its copolymer films using the spin coating and LB methods [ 39 ]. Several studies have reported that PVDF, along with other materials, form a composite or combination of materials that offer the advantages of both materials [ 22 , 23 , 24 , 28 , 29 , 31 , 33 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Biopolymer Coatings For Surface Modificationmentioning
confidence: 99%
“…Non-reactivity is necessary for the fabrication of surgical meshes and sutures, yet piezoelectricity is essential for wound-healing applications. As a result, this material is regarded as being appropriate for many biomedical applications, such as tissue engineering [24][25][26][27][28][29], detection of physiological signals [58][59][60][61][62], and the production of antibacterial and antifouling materials [63][64][65][66][67][68]. PVDF does not generate smoother films and problems of being adhesive with other substrates, which makes it challenging to employ in the production of coatings for use in the biomedical industry.…”
Section: Polyurethane (Pu)mentioning
confidence: 99%
“…In tissue engineering, it is essential to supply suitable biointerfaces, comprehend the mechanism by which these biointerfaces integrate with tissues, and exercise control over the features of these biointerfaces [24][25][26][27][28][29]. This control is of utmost significance in the process of developing new methods for the delivery of drugs or biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…As a biocompatible material with excellent chemical stability, PVDF is useful in many medical applications that can take advantage of the pyroelectricity and piezoelectricity of PVDF and its copolymers, including human physiological signals detection [214][215][216][217], tissue engineering scaffolds [218][219][220][221][222][223], and antifouling ultrafiltration membranes [224][225][226][227][228].…”
Section: Medical Applicationsmentioning
confidence: 99%